Masonry for Sustainable Construction - Almusaed, Amjad; Almssad, Asaad (IntechOpen, 2023)
Durability, fire resistance, local economic growth, and historic preservation are just a few advantages that masonry has as a sustainable building material. Its usage in environmentally friendly building practices can lessen the environmental effect of buildings and provide durable constructions that can withstand the test of time. Also, masonry may be modified over time to meet evolving requirements and usage. Masonry is a versatile and adaptable building material because of its modular design, which enables the addition of new areas or the removal of existing ones. Technological advancements have created new issues, such as climate change, aging infrastructure, unorganized labor forces, and depleting resources. By summarizing the most essential and valuable applications of the numerous duties and tasks that distinguish modern cities, this book presents a well-grounded vision for the sustainable structures we need to live in. The book simultaneously illustrates and analyzes various ideas and ways to treat the subject of contemporary sustainable buildings and their impacts on human existence, using the notion of sustainability for the most common construction materials used in masonry.